EFFICACY TESTING OF ANTIMICROBIAL PRESERVATIVES ON COSMETIC PRODUCTS (FACE MASK X) THROUGH MICROBIAL CHALLENGE TEST AND IN-USE TEST METHOD - Dewantara Yoga, Benedictus
Along with the growth of the cosmetic industry sector in the world and Indonesia, the quality and safety of cosmetic products must also always be controlled and ensured that they are safe from the risk of containing hazardous ingredients. Face mask as one of the skincare products contains various ingredients that can be a source of nutrition for microorganisms so that this product becomes more susceptible to contaminants. Preservatives are usually added to avoid the growth of microbial contaminants in cosmetic products. Preservative efficacy testing is generally carried out to show the effectiveness of antimicrobial activity used in cosmetic products. One of the most commonly used methods is the microbial challenge test based on the EU (European Pharmacopoeia) and FI (Indonesian Pharmacopoeia). This study aims to confirm the adequacy of the preservative concentration of DMDM Hydantoin in the skincare product (Face Mask X) by comparing the microbial challenge test and the direct user test method. In this study, efficacy tests were carried out on 3 variations of the sample formula for face mask X, each containing different concentrations of preservatives with codes 01, 02, and 03 respectively, and packaged in tubes and pots. Challenge test was conducted based on European Pharmacopoeia and Indonesian Pharmacopoeia using these microbes: Escherichia coli ATCC 8739, Staphylococcus aureus ATCC 6538, Pseudomonas aeruginosa ATCC 9027, Candida albicans ATCC 10231, and Aspergillus niger ATCC 16404. The face mask X sample was then distributed to 90 volunteers to be rubbed regularly on the palms of their hands for 8 weeks during the in-use test. The isolated microbes obtained from the returned product were then analyzed microscopically, done a sequencing process, analysis the sequencing results and phylogenetic tree were carried out. The results showed that the optimal age of E. coli, S. aureus, P. aeruginosa, C. albicans, and A. niger were respectively: 3 hours; 6 hours; 6 hours; 14 hours; and 144 hours. Based on the results of the microbial challenge test, the face mask X sample variation 1 gave a higher log reduction in the number of microbial cells compared to variations 2 and 3, and all of face mask X sample formulas met the accepted standard of passed-A (for variations 1 and 2) and passed -B (for variation 3) according to EU and all variations passed according to FI. All of these products also had an acceptable standard of marginally preserved in pot packaging and well-preserved in tube packaging, except for 1 product which was categorized as failed because there were Gram-negative bacteria in variations of 3 tube packages. In addition, 4 types of microbial isolates were obtained from direct user tests. The contaminants found were from the genus Pseudomonas sp., Macrococcus sp., Staphylococcus sp., and Micrococcus sp. Overall, it can be concluded that the formula for the concentration of preservatives in the sample face mask X which has the best efficacy among the three sample formulas is sample face mask X variation 1 which contains a high concentration of preservatives. In addition, the formula for face mask X variation 2 can be considered to have an adequate concentration of preservatives to be used in face mask X products based on the results of challenge tests and in-use tests.